2012
DOI: 10.1111/j.1750-3841.2012.02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile and Sensory Characteristics of Table Eggs from Laying Hens Fed Hempseed and Hempseed Oil

Abstract: This study provides evidence that HS and hempseed oil (HO) can safely be utilized as feed ingredients for laying hens to produce table eggs that are enriched in essential fatty acids. Additionally, the eggs procured from these hens had similar aroma and flavor compared to eggs from hens not fed any hemp. The greater the dietary hemp inclusion, the more pigmented the resulting yolks became in terms of darkness, redness, and yellowness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 29 publications
7
64
1
2
Order By: Relevance
“…Overall, the data from the current study supports the contention that laying hen diets can contain up to 20% HS and 12% HO without affecting measures of hen productivity or specific measures of egg and eggshell quality. Additional support for the use of hemp products in laying hen diets is realized by way of data supporting the lack of negative effects on the sensory parameters of the resultant eggs (Goldberg et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the data from the current study supports the contention that laying hen diets can contain up to 20% HS and 12% HO without affecting measures of hen productivity or specific measures of egg and eggshell quality. Additional support for the use of hemp products in laying hen diets is realized by way of data supporting the lack of negative effects on the sensory parameters of the resultant eggs (Goldberg et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Variability in egg weight (10.8%) among different sources can affect different parts of eggs and quality of eggs as well as the consumer desire for eggs as consumer typically prefers larger eggs (USDA, 2000). Difference in eggs weight, on the other hand, could be attributed to age and stain of hens (Zita et al, 2009;Alsaffar et al, 2013), dietary protein/amino acids, energy and fat/fatty acids, housing density and housing condition (cages vs floor), health status, environmental stress and feed intake (Attia et al, 1994;Ahmadi and Rahimi, 2011;Goldberg et al, 2012;Bovera et al, 2014). It should be mentioned that hens in A, B, C and D groups were kept under similar common management and husbandry practice for laying hens under commercial table egg production.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in the quality and nutritional values of eggs has a significant impact on consumers' health; simultaneously, welfare and many other factors can affect egg quality. These factors include the breed and strain of layers (Cook and Briggs, 1977;Kiiskinen and Helander, 1998;Elkin, 2004;Zita et al, 2009;Kucukyilmaz et al, 2012), dietary composition (Calislar and Kirik, 2009;wiatkiewick et al, 2010;Goldberg et al, 2012), birds' health, environmental condition and storage, processing and handling of eggs (Ryu et al, 2011;Zhang et al, 2011;Khan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Nowadays, several strategies to increase the levels of n-3 PUFAs in different types of food have been applied and evaluated, such as the n-3 PUFA-enrichment of poultry meat with algal biomass, 25 baked goods with flaxseed flour, 26 infant formula with marine oils, 27 and chicken eggs with oilseeds and fish oils. 28,29 Additionally, recently published studies involving Nile tilapia fed a diet supplemented with different seed oils showed an expressive increase of n-3 PUFAs in their fillets and a decrease in the n-6/n-3 ratio. 30,31 In the present study, we evaluated the incorporation of LNA, the effect on EPA and DHA levels and lipid nutritional quality indexes in the fillets of Nile tilapia fed a diet supplemented with Japanese grape seed oil (JGSO).…”
Section: Introductionmentioning
confidence: 99%